Clinical Utility of Implantable Loop Recorders. Issue 2 (March 2014) - Houmsse, Mahmoud; Ishola, Abiodun; Daoud, Emile G.
Abstract : : Implantable loop recorders provide the highest sensitivity and accuracy of diagnosing cardiac arrhythmia that results in cardiac syncope. When bradyarrhythmia or tachyarrhythmia, including atrial fibrillation, is detected, appropriate secondary prevention therapy will be implemented, which will impact the long–term clinical outcome. An implantable loop recorder enables the clinician to record for a longer period of time, which increases the likelihood of detecting cardiac arrhythmia. Currently, this technology is being evaluated to diagnose a cardiac etiology of ischemic stroke and to optimize atrial fibrillation management that will predict the success of rhythm control and prevent thromboembolic events. This article reviews implantable loop recorder technology, and discusses the current indications, the outcomes of clinical studies and ongoing current studies, and future technological improvements.